(untitled) (Contemporary Journal of Social Science Review, 2026)
This research was aimed at investigating the relationship between behavioral severity and stress experienced by the therapist as well as mediating role of coping strategies among therapists dealing with children with developmental and behavior disorders in Pakistan. The research design used was quantitative and cross-sectional, 250 therapists (ABA therapists, behavior therapists, special education teachers, speech therapists, and clinical psychologists) working in autism centers and rehabilitation institutions in large cities of Pakistan were used. Child behavioral severity, child coping strategies, and therapist stress were measured using standardized measures; the Aberrant Behavior Checklist (ABC), Brief COPE Inventory, and Perceived Stress Scale (PSS). The IBM SPSS Statistics and PROCESS Macro were applied to data to analyze them with the help of descriptive statistics, the Pearson correlation, the regression analysis, and the mediation analysis. The result indicated that there was significant positive correlation between child behavioral severity and stress of the therapists (r = .61, p < .001). The therapist stress was negatively correlated with adaptive coping strategies and positively correlated with maladaptive coping strategies. The mediation analysis also showed that coping strategies also played an important mediating role between child behavioral severity and therapist stress. It was found that therapists who adopted adaptive coping styles had less distress in mind though subjected to intimidating child behaviors. The research emphasizes the role coping-based interventions, stress management programs, and institutional support mechanisms played in supporting the therapist working in the rehabilitation setting. The results are an addition to the sparse Pakistani research on therapist mental health and have some practical implications on how to enhance the therapist wellbeing and efficacy of therapy. It is suggested that future research should employ longitudinal designs and consider other psychological factors like resiliency and emotional intelligence.